2022
DOI: 10.1109/jssc.2022.3140414
|View full text |Cite
|
Sign up to set email alerts
|

HERMES-Core—A 1.59-TOPS/mm2 PCM on 14-nm CMOS In-Memory Compute Core Using 300-ps/LSB Linearized CCO-Based ADCs

Abstract: We present a 256 × 256 in-memory compute (IMC) core designed and fabricated in 14-nm CMOS technology with backend-integrated multi-level phase change memory (PCM). It comprises 256 linearized current-controlled oscillator (CCO)-based A/D converters (ADCs) at a compact 4-µm pitch and a local digital processing unit (LDPU) performing affine scaling and ReLU operations. A frequency-linearization technique for CCO is introduced, which increases the maximum Manuscript

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 46 publications
(41 reference statements)
1
40
0
Order By: Relevance
“…Recently, Khaddam‐Aljameh et al [100,101] reported about a 256 × 256 in‐memory core based on the 14 nm technology with multilevel PCM. They combined 256 linearized analog‐digital converters based on current controlled oscillators with a local digital processing unit and showed reliable matrix‐vector multiplication over 1 GHz, as well as a high classification accuracy when this in‐memory computation core was applied for deep learning.…”
Section: Pcm For Non‐von Neumann Computersmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Khaddam‐Aljameh et al [100,101] reported about a 256 × 256 in‐memory core based on the 14 nm technology with multilevel PCM. They combined 256 linearized analog‐digital converters based on current controlled oscillators with a local digital processing unit and showed reliable matrix‐vector multiplication over 1 GHz, as well as a high classification accuracy when this in‐memory computation core was applied for deep learning.…”
Section: Pcm For Non‐von Neumann Computersmentioning
confidence: 99%
“…I G U R E 7 (a) Resistance distribution of four states in phase-change memory (PCM) cells; (b) the corresponding ramp-down current pulses.From Xie et al[81], originally published under a CC-BY license.signals at the same time, which necessitates complex algorithms with high memory requirements, making it one of the areas where inmemory computing is expected to reduce memory and computing resources. They showed similar accuracy of the chosen compressed sensing algorithm on their prototype multilevel PCM chip consisting of more than 256 k PCM devices, as compared with fixed-point implementation with matrix and vector elements quantized to 4 bit.Recently, Khaddam-Aljameh et al[100,101] reported about a 256 × 256 in-memory core based on the 14 nm technology with multilevel PCM. They combined 256 linearized analog-digital converters based on current controlled oscillators with a local digital processing unit and showed reliable matrix-vector multiplication over 1 GHz, as well as a high classification accuracy when this in-memory computation core was applied for deep learning.The temperature dependence of such in-memory computing devices based on PCMs was discussed by Boybat et al [102] They investigated the conductance states for multilevel PCMs in which synaptic weights for deep learning applications were stored by characterization of a large number of 10,000 doped Ge 2 Sb 2 Te 5based PCMs and modeled the temperature dependence of the conductance states.…”
mentioning
confidence: 99%
“…Resistance-based IMC cores, and more specifically those based on phase-change memory (PCM) devices, have recently shown promising results [43]. In a resistance-based IMC core, we can encode certain values as conductances of PCM devices placed in a mesh-like array.…”
Section: B In-memory Computingmentioning
confidence: 99%
“…In this context, filamentary memristors and phase change memories can be used in a very elegant and energy-efficient way. These devices can act as analog synaptic weights enabling neural network multiply-and-accumulate operations directly in memory by relying on Ohm's law and Kirchoff's current law [1][2][3][4][5][6][7] . Low-power systems of this kind could provide essential services: for example, medical devices could analyze patient measurements and detect life-threatening emergencies or automatically adjust treatment.…”
Section: Introductionmentioning
confidence: 99%